2021
DOI: 10.3389/fcell.2021.661599
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Pathogenic Variants of TJP2 Gene and the Underlying Molecular Mechanisms in Progressive Familial Intrahepatic Cholestasis Type 4 Patients

Abstract: Progressive familial intrahepatic cholestasis (PFIC) is an autosomal recessive inherited disease that accounts for 10%–15% childhood cholestasis and could lead to infant disability or death. There are three well-established types of PFIC (1–3), caused by mutations in the ATP8B1, ABCB11, and ABCB4 genes. Biallelic pathogenic variants in the tight junction protein 2 gene (TJP2) were newly reported as a cause for PFIC type 4; however, only a limited number of patients and undisputable variants have been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Basically, these differential proteins of MCF7 responding to culturing in a glucose-rich medium are mainly involved in the two functions, membrane-related such as DNAJC1, NDUFA2, TJP2, TNPO2, and PLEKHF2 and nucleus-located such as HDAC1 and TARDBP, and are assumed to be involved in the formation of protein complexes. Their dynamic behaviors of protein abundance during the 4 h culturing period presented in Figure E, however, exhibited quite diverse modes.…”
Section: Resultsmentioning
confidence: 99%
“…Basically, these differential proteins of MCF7 responding to culturing in a glucose-rich medium are mainly involved in the two functions, membrane-related such as DNAJC1, NDUFA2, TJP2, TNPO2, and PLEKHF2 and nucleus-located such as HDAC1 and TARDBP, and are assumed to be involved in the formation of protein complexes. Their dynamic behaviors of protein abundance during the 4 h culturing period presented in Figure E, however, exhibited quite diverse modes.…”
Section: Resultsmentioning
confidence: 99%
“…Based on clinical presentation, liver biopsies, and molecular testing, our patient was diagnosed with PFIC 4. Few reported cases were available in the literature [5,[7][8][9][10][11]. The clinical manifestations of PFIC 4 in the neonatal period range from mild neonatal cholestasis and obstructive jaundice [4] to a more severe clinical course [4,5,7].…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports of PFIC 4 to date [5,[7][8][9][10][11]. We report the first PFIC 4 case in the Middle East involving a 46-day-old male infant with chronic cholestatic liver disease and low gammaglutamyltransferase (GGT) diagnosed with TJP2-related PFIC 4 and treated with a liver transplant.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there were dilated tubules, reduced microvilli density, and decreased expression of the tubule membrane transporter BSEP ( Xu et al, 2021 ). In vitro experiments have shown that inhibiting TJP2 expression using siRNA can inhibit the proliferation of L02 and HepG2 cells, induce cell apoptosis, and cause microfilament disturbance ( Tang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%